Assessment of Vocational Skills Development and Small Scale Enterprises Programmes of National Directorate of Employment for Self-Reliance among Youths in North-East, Nigeria - Yahaya, A.; Inuwa, U.; Hamza, , S. (Kashere Journal of Education, 2021)
The study assessed vocational skills development and small scale enterprises programmes of national directorate of employment for self-reliance among youths in north-east, Nigeria. The study adopted a survey research design which is purely quantitative, using a structured questionnaire which was administered to 418 NDE trainees that were proportionately selected from the NDE training centers in North-east, Nigeria. Data collected was analyzed using mean, standard deviations and independent samples t-test. The findings of the study revealed among others that vocational skills development and small scale enterprise programmes trained youths (graduate and non-graduate NDE trainees) for self reliance. the findings of the study suggest that the parents should always encourage their children specifically youths to enroll into various NDE programme such as vocational skills development and small scale enterprise this will enable them to receive necessary skills and training for self-reliance. Moreover, the teachers of higher institutions should also encourage students to enroll after graduation into various NDE programme such as vocational skills development and small scale enterprise in order to obtained additional skills and training for self-reliance.